THE POLEMIC OF HOUSEHOLD WORK BETWEEN WOMEN AND MEN IN THE PERSPECTIVE OF GENDER EQUALITY: Polemik Pekerjaan Rumah Tangga Antara Perempuan dengan Laki-Laki dalam Perspektif Kesetaraan Gender - Hasan Subhani; Pendi Nurul Azmi (Tunas Harapan Ummat Foundation, 2026)
This study discusses the issue of household work from the perspective of the Quran through a gender analysis. Socially, Muslim societies tend to regard domestic work as the responsibility of women, while men are positioned in the public sphere. Such perceptions are largely influenced by patriarchal cultural constructions that also shape interpretations of Quranic verses concerning marital relations. Through a feminist tafsir approach, this study seeks to re-examine verses such as Q.S. An-Nisā’ [4]: 34, Q.S. At-Taubah [9]: 71, Q.S. Al-Baqarah [2]: 187, and Q.S. Ar-Rūm [30]: 21 to explore how the Quran explains the concepts of justice and reciprocity within family life. The findings indicate that the Quran never explicitly assigns household work as the obligation of women. On the contrary, it emphasizes the principles of musyārakah (partnership), mawaddah wa raḥmah (affection and mercy), and mubādalah (mutuality) as the foundation of marital relationships. Therefore, domestic work should be understood as a shared responsibility grounded in the values of justice, love, and mutual respect as taught by the Quran. The study aims to reinterpret Quranic verses often associated with male dominance, emphasizing instead their moral message of partnership and mutual responsibility.